DESIGN OF OPERATOR STATION WORK ON LINE PACKING PT. X SURABAYA - Fadilatus Sukma Ika Noviarmi; Martina Kusuma Ningtiyas (Universitas Darussalam Gontor, 2018)
The design or redesign of the work station take into account of benefits as well as the purpose of the components of the working system involved: human, equipment, and physical working environment. The main purpose of this research was to redesign the work station based on ergonomic principle. This research was a descriptive research conducted in one cosmetics factory in Surabaya with 10 operator samples in packing line in morning and afternoon shift. Redesign of the work station based on measurement of physical dimension of work station and anthropometry of operator body. The result of this research is known that some operator work station in doing packing activity less pay attention to ergonomic principles so there need to be redesain work station. Working conditions after the redesign of work stations to be better with the size of work equipment such as table (line conveyor), chairs, and layout boxes that have been adjusted to the anthropometry data of operator. Comfortable working conditions will increase the productivity of the operator's work. Keywords: Design, work station, ergonomics, operator